Combination and comparison of two models in prognosis of pulmonary embolism: Results from TUrkey Pulmonary Embolism Group (TUPEG) study - Ozsu, Savas; Ozlu, Tevfik; Senturk, Aysegul; Ucar, Elif Yilmazel; Kirkil, Gamze; Kadioglu, Esra Ekbic; Uysal, Ahmet (Pergamon-Elsevier Science Ltd, 2014)
Background: Clinical parameters, biomarkers and imaging-based risk stratification are widely accepted in pulmonary embolism(PE). The present study has investigated the prognostic role of simplified Pulmonary Embolism Severity Index (sPESI) score and the European Society of Cardiology (ESC) model. Methods: This prospective cohort study included a total of 1078 patients from a multi-center registry, with objectively confirmed acute symptomatic PE. The primary endpoint was all-cause mortality during the first 30 days, and the secondary endpoint included all-cause mortality, nonfatal symptomatic recurrent PE, or nonfatal major bleeding. Results: Of the 1078 study patients, 95 (8.8%) diedwithin 30 days of diagnosis. There was no significant difference between non-low-risk patients ESC [12.2% (103 of 754;)] and high-risk patients as per the sPESI [11.6% (103 of 796)] for 30-day mortality. The nonfatal secondary endpoint occurred in 2.8% of patients in the the sPESI low-risk and 1.9% in the ESC low-risk group. Thirty-day mortality occurred in 2.2% of patients the sPESI low-risk and in 2.2% the ESC low-risk group (P = NS). In the present study, in the combination of the sPESI low-risk and ESC model low-risk mortality rate was 0%. Conclusions: The sPESI andthe ESCmodel showed a similar performance regarding 30-daymortality and secondary outcomes in the present study. However, the combination of these two models appears to be particularly valuable in PE. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Low-Risk Patients; Severity Index; Stratification; Outpatient; Biomarkers; Diagnosis; Selection